2014
DOI: 10.1007/s00330-014-3530-1
|View full text |Cite
|
Sign up to set email alerts
|

Computed tomography, magnetic resonance imaging and FDG positron emission tomography in the management of vulvar malignancies

Abstract: • False-positive metastatic PLN or distant metastasis PET findings are not uncommon. • CT/MRI has value in the management of vulvar malignancies. • PET can be supportive when metastasis is suspected by CT/MRI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
42
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 28 publications
2
42
0
2
Order By: Relevance
“…Furthermore, we showed that ultrasound performance was comparable, if not better, to that of CT scan and both single‐ and dual‐phase FDG‐PET/CT found in our series, and reported in the literature, for predicting LN status. It is worth underlining that such a high predictive power of ultrasound examination can be guaranteed only by dedication and specific training of the ultrasound examiner in vulvar cancer diagnosis and treatment.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Furthermore, we showed that ultrasound performance was comparable, if not better, to that of CT scan and both single‐ and dual‐phase FDG‐PET/CT found in our series, and reported in the literature, for predicting LN status. It is worth underlining that such a high predictive power of ultrasound examination can be guaranteed only by dedication and specific training of the ultrasound examiner in vulvar cancer diagnosis and treatment.…”
Section: Discussionsupporting
confidence: 78%
“…Currently, several imaging methods are available for this purpose, comprising ultrasound examination, ultrasound-guided fine-needle aspiration cytology (FNAC), computed tomography (CT), magnetic resonance imaging (MRI) and fluorodeoxyglucose-positron emission tomography (FDG-PET) 12,[17][18][19][20][21][22][23][24] . In particular, ultrasound examination shows a relatively high sensitivity and specificity, while at the same time it is cost-effective, easy-to-learn and easy-to-perform, and it does not require use of radiation or contrast agents 17 .…”
Section: Introductionmentioning
confidence: 99%
“…On retrospective review of 5/7 false-positive cases, the group state that FP pelvic adenopathy most likely corresponded to urinary FDG excretion; and FP thoracic lymph node enlargement probably represented reactive adenopathy given the typical spread of vulvar cancer. They concluded that PET can have a positive impact, however should be interpreted with caution as false positive lymph node and distant metastasis findings are not uncommon [18]. …”
Section: Discussionmentioning
confidence: 99%
“… Cervical cytology, and colposcopy of the cervix and vagina, if applicable, due to the association of HPV‐related cancers with other squamous intraepithelial lesions. Full blood count, biochemical profile, liver profile, and HIV testing. Chest X‐ray. CT or MRI scan of the pelvis and groins may be helpful, especially for locally advanced tumors, to detect any enlarged lymph nodes in the groins or pelvis, erosion into underlying bone, or other metastases . In addition, CT or MRI could be useful in further treatment planning. 18 F fluorodeoxyglucose ( 18 F‐FDG) positron emission tomography with computed tomography (PET‐CT) can more effectively assess and detect inguinofemoral lymph node involvement compared with CT, influencing the planning of primary surgery and inguinal lymph node dissection to determine the optimum surgical extent without sentinel lymph node dissection and use of frozen sections . Additionally, PET‐CT might be used with larger tumors when metastatic disease is suspected or in the recurrence scenario …”
Section: Management Of Squamous Cell Carcinomamentioning
confidence: 99%